Four Corners States Biomonitoring Consortium: Lessons Learned During Implementation. (September 2017) - Chaudhuri, Sanwat N.; Broekemeier, Megan; Butler, Carrie; Coyle, Alexander; Iuliano, Kayla; James, Katherine A.; LeFevre, Sam
Abstract : Building on a history of collaboration in environmental public health and biomonitoring activities, laboratory and environmental epidemiology leaders in Arizona, Colorado, New Mexico, and Utah created the Four Corners States Biomonitoring Consortium, which is now in its third year of activities. In this article, we briefly highlight some lessons learned during the implementation phases of the consortium, including the processes of collaborating to identify common environmental exposure concerns, prioritizing those concerns, identifying cohorts and communities with potential risks of excessive exposure, developing a model for conducting exposure investigations, and the challenges presented during the implementation phases and early fieldwork activities. Detailed information on these topics can be found atwww.4csbc.org . The advantages of collaborating with, and leveraging the resources of, state Environmental Public Health Tracking Networks and Public Health Emergency Preparedness programs are discussed. Using one example from the early stages of this work, we also discuss the potential of biomonitoring as a vehicle for empowering the public to make informed choices to control their exposures and to influence public health decisions, support science-based environmental health policy and program development, and respond to emerging environmental exposure concerns.